(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Plastics are useful product but their disposal as a waste had become a serious problem, especially in India. Recycling of plastic waste into useful products is one of the solution for its disposal. Plastic can be used in the bituminous (asphaltic) pavement construction which may help in reducing the permanent deformation in the form of rutting the Pavement surface and also, its use in bituminous binders helps in the protection of our environment. PET (Polyethylene Terephthalate) is a form of plastic waste which is now being used as packaging material for a wide range of products and also in the packing of carbonated beverages. In this study, the effects of PET on various properties of the bitumen are discussed in details. PET was added @ 2.5% increment to the bitumen from 0% to 15% and various tests such as ductility test, penetration test, specific gravity test, softening point, flash and fire point and thin film oven test (TFOT) were performed. From the results of our study, it was inferred that the modified bitumen inherits better performance when compared to the virgin bitumen. The most effective percentage of Polyethylene Terephthalate (PET) waste in our study was seen between 10 to 12.5% by weight of the bitumen, beyond 12.5%properties like ductility of bitumen gets reduced. Hence, PET could be used more effectively up to the percentage of 12.5%.